Dashboard Design for Monitoring Health, Safety, and Security as Part of Social Sustainability in the Mining Industry Holding Group - Aqsho, Ziq Izza El; Maghfiroh, Intan Sartika Eris; Setiawan, Nanang Yudi (Faculty of Computer Science (FILKOM) Brawijaya University, 2026)
Social sustainability is a critical aspect of sustainable development, particularly in the mining industry, which carries high risks related to occupational health and safety. This study aims to design a Health, Safety, and Security (HSS) dashboard to support data-driven decision-making within a mining industry holding group. The development follows a User-Centered Design (UCD) approach and is evaluated using the Dashboard Assessment Usability Model (DATUS). The dashboard was developed iteratively by applying principles of the Visual Information Seeking Mantra (VISM), Gestalt, and Data Storytelling. It comprises 32 HSS indicators grouped into four main modules: KPI, Health, Safety, and Security. Testing results show high effectiveness, with a task completion rate of 98.9%, an error rate of 1.1%, and an 18.04% improvement in task completion time during the second session. User satisfaction scored 88.3 out of 100. These results indicate that the dashboard effectively enhances monitoring and strategic decision-making related to social sustainability in the mining sector.